Comparing Student high and low Reading Performance with Differentiated Digital Reading Materials - Paleczek, Lisa; Ender, Daniela; Kogler, Andrea; Seifert, Susanne (European Conference on e-Learning)
The present study investigates eight Grade-4 classes (9- to 12-year-olds, 52.1% girls) who worked on at least 10 lessons using project RegioDiff material. The study focuses on one of these lessons (including nine text passages and corresponding tasks) and on students with low (19 students, percentile <15) and high reading skills (29 students, percentile > 70). While students were working with the material, screencasts were recorded (30h). The construct “task performance” (processing time, response accuracy, and task engagement) was then analysed using the screencasts.
The analysis revealed that the two groups differed significantly in the processing time of two tasks, but not in the total time spent on all nine tasks. Significant differences were revealed also for general task engagement. Task engagement was highly correlated with processing time. Participants with higher reading skills spent more time on the tasks and were more engaged than participants with lower reading skills. However, we did not find any differences in terms of answer accuracy. This indicates that task difficulty and student reading skills were well matched.
The study also shows how tasks may be adapted or augmented in order to match the learning environment more closely to student learning needs.

Bending and Bowing: How Teachers Adapt a Vocabulary-Based Reading Program to Their Students Needs - Kulmhofer-Bommer, Andrea; Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Journal of Education)
This paper investigates the implementation of a reading program designed for third grade elementary school classrooms in Austria. Using a mixed-methods approach, lesson types were identified, respective class compositions analyzed, and the effects on students’ reading gains examined. The results show that the lesson types seem to reflect learner group needs as students in the different lesson types profited similarly from the reading program. This supports the hypothesis that reading is a highly individualized process and leads to the conclusion that the instructional approach of the reading program investigated supports teachers in conducting reading lessons tailored to their students’ needs.
Keywords: Education

A feasibility study of digital content use in inclusive, Austrian primary school practice - Paleczek, Lisa; Ender, Daniela; Berger, Jessica; Prinz, Katharina; Seifert, Susanne (International Journal of Educational Research)
Keywords: Education

First-year university students' self-regulated learning during the COVID-19 pandemic: a qualitative longitudinal study - Liebendörfer, Michael; Kempen, Leander; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract When the COVID-19 pandemic began, many universities switched to fully online teaching. This unexpected switching to online teaching was challenging for both teachers and students, and restrictions that were put in place because of pandemic made this challenge even greater. However, new ways of teaching might also open new opportunities for students’ learning. The research question driving our study was as follows: how do students regulate their learning and specifically their choice of resources and peer learning in university mathematics classes that are fully taught online as offered during the COVID-19 pandemic? We report on a longitudinal, qualitative study in which students recorded a brief audio diary twice a week over one whole semester (14 weeks). We focused on three students who completed 70 interviews in total and finished the semester with varying degrees of success. The results show how the students structured their studying (e.g., the roles that deadlines or synchronous teaching events played). They illustrate the strengths and limitations of digital materials provided by the lecturer and the use of complementary media. Further, the pandemic uncovered the double-edged role of simple, often anonymous exchanges (e.g., via Discord servers), with few binding forces for either side, and the significance of stable learning partnerships for students’ success. Our research highlights aspects that should be focal points when comparing traditional instruction and online instruction during the pandemic from a self-regulatory perspective. Practical implications refer to how these aspects can be combined sensibly in fully online courses, but also in blended learning contexts.
Keywords: General Mathematics; Education

Exploring the Perceived Relevance of University Mathematics Studies by First-Semester Teaching Students - Büdenbender-Kuklinski, Christiane; Hochmuth, Reinhard; Liebendörfer, Michael (International Journal of Research in Undergraduate Mathematics Education)
Abstract As earlier research results suggest that many mathematics teaching students criticize a missing relevance in their studies, we explore explanations and interrelationships of their relevance assessments. We aim at finding out how one could support the students in attributing relevance to their study programs. A two-fold model for relevance assessments in mathematics teacher education is proposed, consisting of relevance content and relevance reasons. We investigate students' relevance perceptions of mathematical topics and of topics’ complexities, as well as their rating of individual and societal/ vocational relevance reasons, all in relation to their perception of the relevance of their overall program of study. Contrary to earlier research findings, our results suggest that mathematics teaching students already do attribute relevance to many content areas and that a preparation for the teaching profession is not the only reason for them to assign relevance. There also seem to be many students who would attribute relevance if they could develop as individuals and pursue their interests. We suggest that giving students opportunities to set individual priorities in their studies could hence support their relevance assessments. As low relevance assessments seem to be connected to students’ motivational problems, students might profit from motivational support, as well.
Keywords: Education; Mathematics (miscellaneous)

Frameworks and Methodologies for Search-based Approximate Logic Synthesis - Witschen, Linus Matthias

Survey on methods for early prototyping and validation of technical product ideas - Asmar, Laban; Grigoryan, Khoren; Kuhn, Arno; Dumitrescu, Roman (2022 IEEE 20th International Conference on Industrial Informatics (INDIN))

Ein Ansatz zur Strukturierung von KI-Assistenzen im Model-Based Systems Engineering - Kaiser, Lydia; Schräder, Elena; Bernijazov, Ruslan; Foullois, Marc; Dumitrescu, Roman (Tag des Systems Engineering)

Professionalitätsentwicklung angehender Lehrkräfte - Kirsch, Alexander

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

One-bit target detection in collocated MIMO radar and performance degradation analysis - Xiao, Yu-Hang; Ramirez, David; Schreier, Peter J; Qian, Cheng; Huang, Lei (IEEE Transactions on Vehicular Technology)

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Adaptive Operating Strategy for Induction Motors Under Changing Electrical-Thermal Conditions - Stender, Marius; Becker, Marius; Wallscheid, Oliver; Böcker, Joachim (48th Annual Conference of the Industrial Electronics Society (IECON))

Wave-Schnecken in der Einschneckenextrusion - Dörner, Marius

Untersuchungen zur werkstofflichen Aufbereitung von Post-Consumer-Kunststoffabfällen und Entwicklung eines neuen Aufbereitungsverfahrens - Helmlinger, Lars René

Ein Beitrag zur InMould-Plasma Technologie zur Oberflächenvorbehandlung im Mehrkomponentenspritzgießwerkzeug - Mühlhoff, Frederik Marvin

Ein Beitrag zum Warmgasstumpfschweißen von Kunststoffen - Bialaschik, Max Oliver

Modellierung der Carbonfaserlängenverkürzung - Malatyali, Hatice

Texte im Deutschunterricht. - Rezat, Sara (12 Perspektiven auf den Deutschunterricht. Wissenswertes für Deutschlehrkräfte.)